SEMIOTIKA ALTRUISME: REPRESENTASI SIMBOL TUBUH DALAM FILM SAMMI, WHO CAN DETACH HIS BODY PARTS - Hana Fadhila Rahmanita; Munawwaroh, Zahrotul; Nurhaqiqi, Hanna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Altruism is fundamentally defined as assisting others without expecting reciprocity. However, within social relations, its meaning shifts, diverging from pure benevolence. While cinema typically idealizes sacrifice, under specific conditions, it can precipitate individual exploitation. The film Sammi, Who Can Detach His Body Parts encapsulates this phenomenon through the symbolism of a detachable body surrendered to others, signifying extreme sacrifice. This study investigates the representation of altruism mediated through body symbolism in the film. Employing a qualitative approach, this research utilizes John Fiske’s semiotic framework, analyzing three distinct levels: reality, representation, and ideology. Data comprising Scenes, dialogues, and audiovisual components were gathered via observation, documentation, and literature review. The findings demonstrate that altruistic acts, represented through bodily detachment, are constructed via character expressions, dialogues, cinematographic techniques, and narrative structures. This representation reveals that while sacrifice is driven by empathy, emotional proximity, and moral responsibility, it simultaneously inflicts physical and psychological repercussions upon the protagonist. At the ideological level, the film depicts a normalization of sacrifice that obscures the boundary between sincerity and exploitation, positioning altruism not merely as a humanitarian value, but as a practice highly susceptible to manipulation within social relations.